The assistance integrality in the prenatal attention context - Raimunda Maria de Melo; Rosineide Santana de Brito; Francisca Patrícia Barreto de Carvalho; João Mário Pessoa Júnior; Sâmara Dalliana de Oliveira Lopes Barros (Rev Rene)
The study focuses on the identification of nurses’ understanding on integrality of health interventions during prenatal care. This is a descriptive and exploratory study, with qualitative approach, held in a health unit in a municipality of Rio Grande do Norte, Brazil. Data collection was processed through a semi structured interview, along with three nurses. The project was approved by the Ethics and Research Committee of Nova Esperança School of Nursing and Medicine, Protocol No. 02/2009. The reports were treated according to the method of content analysis proposed by Bardin, and discussed according to literary findings about assistance integrality. For the interviewees integrality comprises actions aimed at solving health problems of pregnant women from their reality and they recognized the existence of barriers to the application of this principle in prenatal care. Therefore, nurses should be the agent of transformation in the perspective of integrality.